Vorkommen und Zug der Rauhhautfledermaus (Pipistrellus nathusii Keyserling und Blasius, 1839) in Baden-Württemerg ... - Bastian, Hans-Valentin (Die Gesellschaft, 1988)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided. ...